Summary report of QA agency reviews and support and advisory visits - Allal, Amine (HAQAA Initiative, 2023)
This report is part of the Phase Two of the HAQAA Initiative. It synthesizes and analyzes the results of these exercises with a view to informing future use of the review methodology and identifying additional guidance needed for the use of ASG-QA by quality assurance agencies. It attempts, when available, to highlight case examples (among the agencies visited) that can inspire other agencies/departments in the development of their quality assurance policies and methodologies and to give visibility to good practices. This document is based on the analysis of the external review reports (evaluations or consultancy) produced by the experts, which include the analysis of the self-evaluation reports, the results of the surveys and the interviews conducted with the identified stakeholders.
Keywords: Quality Assurance; Higher Education